Marching Band sebagai Media Enkulturasi Nilai Disiplin dan Budaya Prestasi pada Grup Marching Band Simba SD Hj. Isriati Baiturrahman 1 Semarang - Ivan Rafif Orvala; Suharto Suharto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the enculturation process of discipline and achievement culture values in the SIMBA Marching Band extracurricular activities at SD Hj. Isriati Baiturrahman 1 Semarang. The study employed a mixed methods approach with a sequential explanatory design, integrating quantitative and qualitative data. The sample consisted of 32 respondents, including students, a coach, and a supervising teacher. Data were collected through questionnaires, interviews, and documentation. The findings indicate that marching band activities function effectively as a medium for the enculturation of discipline, responsibility, teamwork, and achievement-oriented values. Quantitative data show a high level of agreement (84.62%) regarding the effectiveness of the activity in character development. Qualitatively, the enculturation process occurs through structured training systems, the role modeling of coaches, and collective experiences in both practice and competitions. Students’ motivation, which was initially extrinsic, gradually developed into intrinsic motivation through active participation. Furthermore, students demonstrated significant character development, particularly in terms of discipline, self-confidence, responsibility, and teamwork skills. In conclusion, marching band activities serve not only as an artistic practice but also as a strategic medium for comprehensive and sustainable character development among students.